2019
DOI: 10.30880/ijie.2019.11.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change and Its Impact on Rainfall

Abstract: This paper reviews the climate change impact on rainfall as well as extreme events occurrences. The global extreme weather contributes to the uncertainties of the climate trend and water scarcity problems to the whole world. Thus, numerical models such as General Circulation Models (GCMs) have been developed to simulate the response of the global climate system to the expected increment of the greenhouse gases concentrations. However, the GCM cannot be directly applied to climate change impact studies, hence d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The SDSM application potentially to provide reliable result while having limited sources (Shahid et al., 2017). Its implementations were also well documented and has been successfully tested in numerous studies especially for the long term Malaysia's climate assessment (Noor et al., 2019; Tarmizi et al., 2019; Tahir et al., 2018; Tukimat et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The SDSM application potentially to provide reliable result while having limited sources (Shahid et al., 2017). Its implementations were also well documented and has been successfully tested in numerous studies especially for the long term Malaysia's climate assessment (Noor et al., 2019; Tarmizi et al., 2019; Tahir et al., 2018; Tukimat et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Since 1977, increasingly frequent warm phase occurrences of the El Nino Southern Oscillation (ENSO) have been recorded. This behavior, particularly the prolonged warm period from 1990 to mid-1995, was unprecedented in the previous 120 years and had a substantial impact on rainfall in Malaysia [7]. It indicated that the increment of temperature was affected on reduction of water availability and became worst during dry months.…”
Section: Introductionmentioning
confidence: 98%
“…Changes in the composition of gas emissions in the atmosphere can cause climate change. Climate change can lead an increase in the frequency and intensity of extreme weather events, such as floods and droughts, changes in rain patterns, and increases in temperature and sea levels [2][3][4]. The Intergovernmental Panel on Climate Change-IPCC [5] shows that climate change has occurred with indications of an increase in the average global temperature for the period 1850-1899 to 2001-2005 of 0.76C.…”
Section: Introductionmentioning
confidence: 99%